Domestication and commercialization of non-timber forest products in agroforestry systems: Proceedings of an international conference held in Nairobi, Kenya, 19-23 February 1996 - FAO (FAO, 1996)
This book contains five thematic areas: assessment and monitoring of non-timber forest products; indigenous knowledge and ethnobotany; product development and management; product domestication and adoptions by farmers; and policies and institutional aspects